Pelayanan Pendidikan ABK di TK Inklusi Pelangi Anak Negri Yogyakarta - Hidayah Binsa, Ucik; suismanto, suismanto (ACIECE, 2019)
Education services are closely related to optimizing interactions between parts of the schoolwhere there are payments, training, information technology or infrastructure facilities, especially educational services for children with special needs (ABK) needing full attention in terms of educational services for the smooth running and the success of the process of stimulation of aspects of development in children itself. However, based on observations researchers still found that some schools in PAUD Inclusive levels did not provide maximum educational services as a form of assistance, another case that occurred in the Yogyakarta Rainbow State Children's Inclusion Kindergarten was very concerned about how to serve children with special needs themselves. This study used a qualitative descriptive method carried out in the Yogyakarta Negri Children Inclusion Kindergarten in Yogyakarta. The subjects of the study were all teachers and special needs children (ABK) assistants as well as children who have special needs themselves. Informants were obtained from school principals and child companions with special needs. Data collection techniques with interview methods and documentation. Then analyzed interactively consisting of data reduction, data presentation, and drawing conclusions. Education services for children with special needs in the form of therapy rooms are very important to stimulate children with special needs (ABK), where the practice in the Negro Pelangi Children Inclusion Kindergarten is to treat children one by one in the room with accompanying teachers or psychiatrists according to children's needs. The conclusion of the research is that the provision of services in the form of inviting art experts according to the talents of children with special needs is important, considering that every child must have advantages behind the deficiencies that he bears in order to develop and hone the talent itself, at the Pelangi Inclusion Kindergarten for Negri Children has been applied that matter. Educational services in the form of mentoring are very important to be practiced in inclusive schools where in the Pelangi Inclusive Kindergarten for Negri Children for teachers and children with special needs 1: 3 at a minimum the level of needs of children can still be reached, and providing 1: 1 companion teacher facilities for children whose level of needs is very high for the success of the stimulation of aspects of development itself and the preparation for entering elementary school. Educational services for children with special needs do require quite a lot of funding to help the learning process itself, but the school must be smarter in providing these services without adding the burden on parents of children with special needs